#TITLE_ALTERNATIVE# - BAYU KRISTIAWAN (NIM 13204051), YEHUDA
This final project explains technique for envelope-amplitude and RMS value estimation voltage flicker. The estimation technique is using Hilbert transform. Hilbert transform is employed to obtain information about amplitude envelope and RMS value of voltage flicker. The technique has been tested and evaluated using voltage signal from simulation and voltage signal from laboratory measurement. The simulation using Matlab-Simulink software to result some types voltage flicker modeled as amplitude modulation (AM) signal. The evaluation use two versions of filter order and tested process includes effect of frequency and amplitude variations voltage flicker to the accuracy of the obtained RMS value voltage flicker amplitude. In this evaluation the effect of filter order to time delay is discussed too. The evaluation results show that the proposed technique give high accuracy about its ability to estimate voltage flicker amplitude and RMS value.